2017
DOI: 10.3892/ol.2017.7029
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome biogenesis mediates antitumor activity of flavopiridol in CD44+/CD24‑ breast cancer stem cells

Abstract: Flavopiridol is a synthetically produced flavonoid that potently inhibits the proliferation of human tumor cell lines. Flavopiridol exerts strong antitumor activity via several mechanisms, including the induction of cell cycle arrest and apoptosis, and the modulation of transcriptional regulation. The aim of the present study was to determine the effect of flavopiridol on a subpopulation of cluster of differentiation (CD)44+/CD24− human breast cancer MCF7 stem cells. The CD44+/CD24− cells were isolated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This causes cells to become vulnerable to selective inhibition of rRNA synthesis. Many of the chemotherapeutic agents used in the clinic today, including cisplatin, doxorubicin and flavopiridol, mediate their therapeutic effects, at least in part, through the disruption of ribosome biogenesis [131133].…”
Section: The Nucleolus As a Drug Target For Cancermentioning
confidence: 99%
“…This causes cells to become vulnerable to selective inhibition of rRNA synthesis. Many of the chemotherapeutic agents used in the clinic today, including cisplatin, doxorubicin and flavopiridol, mediate their therapeutic effects, at least in part, through the disruption of ribosome biogenesis [131133].…”
Section: The Nucleolus As a Drug Target For Cancermentioning
confidence: 99%
“…Loss of differentiation (neurogenesis) or stem cell induction genes resulting in active BrCa cell growth in the 3D-EN is consistent with the notion that disseminated tumor cells exhibit stem cell-like properties (28, 29). Differential expression of genes controlling ribosome biogenesis are known to control stem cell homeostasis (30), and indeed, antagonism of this process was shown to inhibit tumor formation induced by CD44 + /CD24 − human BrCa stem cells (31).…”
Section: Resultsmentioning
confidence: 99%
“…Bible et al demonstrated that flavopiridol caused cell cycle arrest at G1 and G2 phases and inhibited CDK2, CDK4, and CDK1 in NSCLC. 21 In addition to this, the IC 50 dose of flavopiridol was determined as 676 nM for CD133+/CD44+ squamous cell lung cancer cells. 8,20 Similar results were observed in HCT8 ileocecal adenocarcinoma, T98G glioblastoma, MCF7 breast adenocarcinoma, and HL60 leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in HCT8 ileocecal adenocarcinoma, T98G glioblastoma, MCF7 breast adenocarcinoma, and HL60 leukemia cells . Erol et al showed that the IC 50 dose of flavopiridol was 500 nM for MCF7 cells and it exhibited antitumoral effects on CD44+/CD24− MCF7 cells at the IC 50 dose by inhibiting translation and the ribosome biogenesis pathway . In addition to this, the IC 50 dose of flavopiridol was determined as 676 nM for CD133+/CD44+ squamous cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%